2021
DOI: 10.2166/wst.2021.084
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis the performance of electrochemical water softening between high frequency electric fields and direct current electric fields based on orthogonal experimental methods

Abstract: Electrochemical water softening has been widely used in industrial circulating cooling water system; however, their low deposition efficiency is the main drawback that limits usage in medium to large enterprises. In this work, the effect of different parameters on the hardness removal efficiency and energy consumption of the electrochemical water softening system is experimental studied, and the performance of water softening applied by high frequency electric field and direct current electric field are compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The random diffusion of H 2 bubbles generated from water electrolysis can cause flow disturbances near the cathode, creating turbulence [63,64], and water flow has also been found to accelerate ion diffusion [65,66]. Utilizing these characteristics, it is deduced that bubble diffusion and water flow can be harnessed to expedite the diffusion of OH − from the cathode surface and effectively separate OH − and H + .…”
Section: Bubbles and Water Flowmentioning
confidence: 99%
“…The random diffusion of H 2 bubbles generated from water electrolysis can cause flow disturbances near the cathode, creating turbulence [63,64], and water flow has also been found to accelerate ion diffusion [65,66]. Utilizing these characteristics, it is deduced that bubble diffusion and water flow can be harnessed to expedite the diffusion of OH − from the cathode surface and effectively separate OH − and H + .…”
Section: Bubbles and Water Flowmentioning
confidence: 99%
“…High frequency power supply has significant advantages in reducing power consumption of electrochemical water softening technology. Lin et al (2021) compared the performance of the electrochemical water softening device in HF electric fields with that direct current (DC) electric fields, and found that HF electric fields can improve the energy utilization rate of the device. Yu et al (Wu et al 2018) used a pulsed power supply for electrochemical water softening treatment.…”
Section: Introductionmentioning
confidence: 99%